(untitled) (American Journal of Islam and Society, 2004)
During the more than 37-year brutal Israeli occupation of the West Bank and Gaza, the numbers of North American Jews voicing their opposition in public have been dispiritingly small. Since the outbreak of the second Intifada in September 2000, however, Jewish anti-occupation activists have become a visible political presence in Jewish politics in the United States and Canada. Such groups as Brit Zedek V’Shalom, the Tikkun Community, and Junity (Jewish Unity for a Just Peace) have spawned dozens of regional chapters across North America. Local groups such as Not In My Name (Chicago), Jewish Voices against the Occupation (Seattle), and Jews for Global Justice (Portland, Oregon) have sprung up spontaneously in almost every major North American city. Numerous ad hoc responses have emerged as well. For example, an “Open Letter from American Jews,” proclaiming opposition to Israeli government policies in the Occupied Territories and bearing 4,000 signatures, has appeared as a full-page advertisement in The New York Times as well as in a dozen more American and British newspapers. While very few of these groups would identify themselves as religiously observant, almost all have invoked a Jewish ethical tradition of social justice, derived from Jewish texts and rabbinical tradition, to make their political point. In his most recent book, Israel and Palestine out of the Ashes, Jewish theologian Marc Ellis posits a more deeply consequential connection between Jewish history, Jewish ethics, and the occupation. According to Ellis, Director of the Center for American and Jewish Studies at Baylor University (Waco, Texas), Israel’s displacement and dispossession of the Palestinian people constitutes such a fundamental transgression of Jewish ethics and morality that it threatens to render Judaism, a religious ...